2012
DOI: 10.1152/ajprenal.00341.2011
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptor activation downregulates organic anion transporter 1 (OAT1) in the renal proximal tubule

Abstract: Liver X receptors (LXRs) play an important role in the regulation of cholesterol by regulating several transporters. In this study, we investigated the role of LXRs in the regulation of human organic anion transporter 1 (hOAT1), a major transporter localized in the basolateral membrane of the renal proximal tubule. Exposure of renal S2 cells expressing hOAT1 to LXR agonists (TO901317 and GW3965) and their endogenous ligand [22(R)-hydroxycholesterol] led to the inhibition of hOAT1-mediated [(14)C]PAH uptake. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…evidence suggests a potential role of LXRs in the regulation of the renin-angiotensin system (RAS) and renal transporters such as Na-Pi transporters (21), OAT1 (22), and epithelial Na + channel (ENaC) (23). In the present study we attempted to define a biological function and signaling of sPRR in the regulation of fluid homeostasis and to test PRR/sPRR further as a target of LXRs in the kidney.…”
Section: Significancementioning
confidence: 99%
“…evidence suggests a potential role of LXRs in the regulation of the renin-angiotensin system (RAS) and renal transporters such as Na-Pi transporters (21), OAT1 (22), and epithelial Na + channel (ENaC) (23). In the present study we attempted to define a biological function and signaling of sPRR in the regulation of fluid homeostasis and to test PRR/sPRR further as a target of LXRs in the kidney.…”
Section: Significancementioning
confidence: 99%
“…However, we cannot rule out the possibility that a change in the open probability of the CFTR channel may account for the inhibition induced by LXR activation. A previous study (13) in the renal proximal tubule S2 cell line expressing human (h)OAT1 has shown that LXR activation downregulates hOAT1 protein levels without altering hOAT1 gene transcription. Recently, Caldas et al (5) reported that the LXR agonists T0901317 and N,N-dimethyl-3␤-hydroxycholenamide inhibited the function of Na ϩ gradient-dependent phosphate transporters by decreasing Pit-2 protein and had no effect on its mRNA level.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that LXRs regulate renal transporters and ion channels, including the Na-P i cotransporter, organic anion transporter (OAT)1, and epithelial Na ϩ channel (ENaC) (5,13,31). Taken together, these results suggest that LXRs have a role in the regulation of renal electrolyte transport.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…LXRs stimulate hepatic lipogenesis by upregulating expression of sterol regulatory element binding protein 1c (SREBP-1c) (Costet et al, 2000;Liang et al, 2002;Higuchi et al, 2008). In addition to regulation of energy metabolism, LXRs have been shown to regulate kidney function by modulating renal transporter and ion channels such as the organic anion transporter 1 (OAT1), epithelial sodium channel (ENaC) and chloride channel (CFTR) (Kittayaruksakul et al, 2012;Soodvilai et al, 2012;Raksaseri et al, 2013) In recent studies, LXR activation has been demonstrated to inhibit inflammatory processes in several cell types (Joseph et al, 2004;Zelcer and Tontonoz, 2006) and has been implicated in oxidative stress responses in lung injury induced by endotoxin through inhibiting the JNK signaling pathway (Gong et al, 2009;Liu et al, 2012). Although LXRs are reportedly expressed in the proximal tubules of the kidney (Zhang et al, 2006) and exhibit antioxidant behaviors, their effects on heavy metal-induced nephrotoxicity have not previously been revealed.…”
Section: Introductionmentioning
confidence: 99%